Rating of Knowledge Management Factors Affecting Construction Company Performance - Eman Mohammed Abdulrahman Alhammadi; Kasim, Rozilah; Sonia Lohana (International Journal of Sustainable Construction Engineering and Technology, 2022)
Construction industry uses project-based activities where project participants are considered as knowledge sources. This makes knowledge management as important factors in project management performance. Thus, this study presents a quantitative study on identifying knowledge management factors affecting Turner construction company performance in UAE. The study identified 32 factors and classified into 4 knowledge management groups namely knowledge leadership, knowledge culture, knowledge process and knowledge technology. A question survey was conducted to the employees of the company requesting them to gauge the influence of each factor to company performance using Likert scale. A total of 350 questionnaire sets were distributed and only 291 valid responses were used for the analysis. The results of the analysis found that in knowledge management leadership group, the most influential factor is KML5 which is Has sufficient resources in project knowledge management activities. For knowledge management culture, the most influential factor is KMC3 which is Rewards employees who create, share, store and use knowledge to perform projects. In knowledge process group, the most influential factor is KMP7 which is Believe in sharing knowledge with others. For the final group that is knowledge technology, the most influential factor is KMT8 which is Responsible for creating project knowledge-sharing technology environment. The result also found that the most influential group is knowledge management leadership group has attained the highest score. For cross tabulation analysis, it was found that leadership and culture related to knowledge management are more pertinent to senior respondents who are holding higher position in the company. This is logic as they need to manage the resources of the company holistically as compare to junior respondents. While junior employees/respondents are more inclined to knowledge management related to processes and technology. These findings are benefitted to the construction company in prioritizing the application knowledge management aspect.